1993
DOI: 10.1080/00480169.1993.35743
|View full text |Cite
|
Sign up to set email alerts
|

Detection of astrovirus in the faeces of cats with diarrhoea

Abstract: Examination by electron microscopy of faeces from two separate cases of young cats with diarrhoea revealed the presence of 28 nm viral particles morphologically consistent with an astrovirus. No visible cytopathic effect was observed when the virus was inoculated into a feline kidney cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Feline astrovirus was first described in cats in 1981 (Hoshino et al, 1981). To date, picornavirus-like particles as well as astroviruses from feces of domestic cats have been described in Australia, England, Germany, New Zealand and the USA (Harbour et al, 1987;Herbst and Krauss, 1989;Hoshino et al, 1981;Marshall et al, 1987;Rice et al, 1993). The impact of AstV infection in cats seems to be low as infection of specific-pathogen free kittens caused two episodes of pyrexia and mild diarrhea (Harbour et al, 1987).…”
Section: Feline Astrovirus (Feastv)mentioning
confidence: 99%
“…Feline astrovirus was first described in cats in 1981 (Hoshino et al, 1981). To date, picornavirus-like particles as well as astroviruses from feces of domestic cats have been described in Australia, England, Germany, New Zealand and the USA (Harbour et al, 1987;Herbst and Krauss, 1989;Hoshino et al, 1981;Marshall et al, 1987;Rice et al, 1993). The impact of AstV infection in cats seems to be low as infection of specific-pathogen free kittens caused two episodes of pyrexia and mild diarrhea (Harbour et al, 1987).…”
Section: Feline Astrovirus (Feastv)mentioning
confidence: 99%
“…This is significant, because MAstV-2 has been directly linked to enteric disease in cheetahs and has been proposed to cause enteric disease in the domestic cat, as well. 3,19 Within the MAstV-2 clade, there appear to be 3 separate groupings of astroviruses present in Alachua County, FL (Fig 1). It is important to note that, even though ACAS samples represented <45% of the sampled population, 15 of the 16 most closely related MAstV-2 sequences were from samples collected at the ACAS site.…”
Section: Brief Communicationmentioning
confidence: 99%
“…8 Subsequent EM-based investigations demonstrated that FAstV may be common in the stool of cats with and without diarrhea. 14,21 Experimental infection with a FAstV strain in specific pathogen-free (SPF) kittens induced enteritis and viral excretion for several days. 7 However, FAstV is not included in the diagnostic algorithms of feline enteric diseases, and its role as a primary pathogen or synergistic agent remains unclear.…”
mentioning
confidence: 99%